Non-linear ASF product distribution over alkaline-earth promoted molybdenum carbide catalysts for hydrocarbon synthesis - Vo, D.-V.N. (2013)
Alkaline earth (Ba, Ca and Mg) promoted Mo carbide catalysts have been synthesized using temperature-programmed carburization for Fischer-Tropsch synthesis. MoO3 precursor was converted completely to final carbide form including Î±- and Î²-MoC1-x phases during carburization runs. Carbide production rate increased with promoter addition whilst a reduction in activation energy of Mo carbide phase formation was observed for promoted catalysts. CO2- and NH3-temperature-programmed desorption runs indicated that Mo carbide catalysts possessed both acid and basic sites with each possessing both weak and strong types. Promoter addition enhanced both CO2 and CO uptake but decreased H2 chemisorption. CO adsorption appeared to be greater than H2 chemisorption with superior uptake and heat of desorption. CO consumption rate improved with promoters in the order; Ca > Ba > Mg > undoped catalysts parallel to the trend for strong basic site concentration and CO uptake. Optimal FT activity was observed at H2 mole fraction of 0.75 for all catalysts. Alkaline-earth promoters increased chain growth probability by up to 63 whilst two different chain growth factors were detected for Ca- and Ba-promoted catalysts and may be attributed to the existence of new FT sites in the CaMoO4 and BaMoO4 phases formed in these two catalysts as confirmed by XRD measurements. Â© 2013 Elsevier B.V. Â© 2012 Elsevier B.V. All rights reserved.